Implementation Of Nursing Care In Schizophrenic Patients With Low Self-Esteem - Arni Nur Rahmawati (Universitas Negeri Gorontalo, 2023)
Schizophrenia is a condition of mental disorders characterized by the disruption of the process of thinking and poor emotional response, this condition is in the form of mind disorders with social dysfunction and speech disorders. One of the negative symptoms found in schizophrenic patients is low self -esteem. Low self -esteem is described as a feeling of worthless, meaningless, and helpless due to negative evaluation in yourself for a long time and continuously. The purpose of this study is to provide nursing care to patients with self -concept disorders: low self -esteem with schizophrenia in the Sadewa room Prof. Dr. Soerojo Magelang. This study uses a case study method with a nursing process approach. Participants in this study were one Schizophrenic patient who experienced a low self -esteem concept disorder in the Sadewa Room of the Soerojo Mental Hospital Magelang. Data collection techniques in this study were carried out with observation, interviews, and documentation studies. The results of this case study indicate that the data in patients describes the diagnosis of nursing low self -esteem, the planned nursing intervention is therapeutic communication with the patient implementation strategy of low self -esteem. The conclusion obtained from this case study is the implementation of therapeutic communication using the implementation strategy 1, 2, 3, 4 and 5 can overcome nursing problems in Schizophrenia patients with low self -esteem for five days of treatment.